Efektivitas Model CIRC Menggunakan Media Scrabble Aksara Jawa Terhadap Hasil Menulis Huruf Jawa - Nadila Windy Afi Febriani; Nur Hanifah Insani (Prodi Pendidikan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2024)
The results of interviews at SMP Negeri 24 Semarang show that the learning process of writing Javanese letters still uses conventional learning models (lectures) using blackboard learning media. This study aims to determine the effectiveness of the CIRC learning model using Javanese script scrabble media on the results of writing Javanese letters in class VIII students at SMP Negeri 24 Semarang. The type of research used is a quasi-experimental design with a non-equivalent control group design. Sampling was conducted in class VIII B (control class) with 32 students and class VIII C (experimental class) with 31 students. Data collection techniques in this study comprised interviews with teachers, observation, learning response questionnaires filled out by experimental class students, documentation, and written tests. This study uses analysis techniques, namely the Independent Sample T-Test test and the N-Gain test. The results of this study indicate that there is an average difference between the learning outcomes of writing Javanese letters in the control class and the experimental class. From this study, it can be concluded that the CIRC learning model using Javanese script scrabble media is significantly effective by 61% in the experimental class and 30% in the control class in improving the ability to write Javanese letters in class VIII students of SMP Negeri 24 Semarang.